Writer's Work/place: The Non/fictional Pedagogical Possibilities of the Canadian Landscape - Land, Mary Sylvia (Université d'Ottawa / University of Ottawa, 2016)
This project considers the role of place in the writing process of Canadian author Monique Polak. Drawing from ideas of literary geography, place-based literacy, and an ecological framework for viewing writing as a social process, this research specifically considers how places are represented in three of her novels written for young adults. This work draws from a representative case study approach, which included conversations with Polak about place, writing, and the intersection of these ideas. By inquiring into the pedagogical possibilities of place as experienced and demonstrated by Polak, educators and researchers can reflect on the role of place in their own work, and consider how teachers and students may benefit from these ideas in their writing as well.
Keywords: Writing; Education; Literacy; Place